1999
DOI: 10.1080/00288233.1999.9513396
|View full text |Cite
|
Sign up to set email alerts
|

Kikuyu (Pennisetum clandestinum) pasture for sheep. 2. Production and nutritional status of ewes with or without lupin (Lupinus albus) supplementation

Abstract: Kikuyu pasture was grazed continuously for 12 months by 20 dry and 40 producing South African Mutton Merino (SAMM) and Merino ewes at a stocking density of 23 ewes ha -1 . Supplementary sweet lupin seed was supplied to one group of producing ewes of each breed during pregnancy and lactation at a rate of 0.5% of the liveweights of the ewes. Rumen fluid samples for the determination of pH, volatile fatty acids (VFA), and ammonia-nitrogen (NH 3 -N) were collected from rumen-fistulated wethers corresponding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The clean yield of Merino ewe wool remained similar to studies from the Elsenburg flocks, which ranged from 71% to 74% (Brand et al, 1999;Cloete et al, 2003;Matebesi-Ranthimo et al, 2017). The clean yield of Dohne Merino was estimated to be 68% (Steinhagen & De Wet, 1986;Cloete et al, 2003).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The clean yield of Merino ewe wool remained similar to studies from the Elsenburg flocks, which ranged from 71% to 74% (Brand et al, 1999;Cloete et al, 2003;Matebesi-Ranthimo et al, 2017). The clean yield of Dohne Merino was estimated to be 68% (Steinhagen & De Wet, 1986;Cloete et al, 2003).…”
Section: Resultssupporting
confidence: 56%
“…The clean yield of Dohne Merino was estimated to be 68% (Steinhagen & De Wet, 1986;Cloete et al, 2003). The clean yield of the SAMM breed has also been presented as 60 -64% of the greasy fleece weight (Brand et al, 1999;Cloete et al, 2003). The yields for Dohne Merino and SAMM fleeces were slightly lower than those reported in the literature.…”
Section: Resultsmentioning
confidence: 95%
“…SAMM ewes produced 3% coarser wool than FW+ Merinos. Previous studies suggested that the fibre diameter of SAMM sheep was 2 -8% higher than that of Merinos (Greeff, 1990;Brand et al, 1999;Cloete et al, 1999). Average fibre diameter of Dohne ewes was 4% finer than that of FW+ Merinos.…”
Section: Resultsmentioning
confidence: 99%
“…In kikuyu grass, histidine, methionine, and cystein are low as compared to other grasses (Reeves et al 1996), and they are regarded as limiting amino acid for dairy cows on kikuyu (Dennison and Phillips 1983). Therefore, the supplement U+BM+RPM may improve the utilization of available NH 3 N for microbial growth (Brand et al 1999). Fulkerson et al (1998) reported a value of 645 g/kg for OM degradation for kikuyu grass and estimated a metabolizable energy of 8.5 MJ/kg DM.…”
Section: Discussionmentioning
confidence: 99%